Recent Oil Spill Challenges That Require More Attention - Marghany, Maged (IntechOpen, 2023)
This book provides a comprehensive overview of oil spill challenges and issues. It addresses the challenges of oil spill behavior, occurrence, cleanup, and much more. Chapter topics include thermal maturity evolution, techniques for cleaning up oil spills, oil spill straining off coastal waters, and the use of radar satellites such as synthetic aperture radar in monitoring oil spills.